A Comprehensive Literature Review of Red Flag Signs and Symptoms for Patients With Early-Onset Colorectal Cancer - Anthony, Anthony; Christian, Christian (International Medical Journal Corp. Ltd, 2024)
Background: The literature on early-onset colorectal cancer (EOCRC) reveals a complex interplay of symptoms, diagnostic challenges, and the need for increased awareness among both patients and healthcare providers. The systematic review by (Mitchell et al., 2007) underscores the necessity of recognizing red flag symptoms such as rectal bleeding and changes in bowel habits, as these are critical for timely diagnosis and intervention. The study highlights that delays in diagnosis can lead to more advanced disease stages, emphasizing the importance of patient education regarding the seriousness of these symptoms. Literature Review: Further investigations, such as those by (Renzi et al., 2016), reveal that many patients present with significant symptoms well before their diagnosis, indicating a gap in timely medical consultation. The findings suggest that abdominal pain and rectal bleeding are prevalent among emergency presentations, yet many patients do not receive timely evaluations, leading to missed opportunities for early intervention.The exploration of risk factors by (R Syed et al., 2019) highlights the challenges faced by younger patients, who often misinterpret their symptoms, resulting in substantial delays in seeking medical attention. This trend is echoed in the study from Indonesia by (Makmun et al., 2021), which notes that abdominal pain is the most common presenting symptom among early-onset CRC patients. The demographic characteristics presented in this study further emphasize the need for targeted screening and awareness initiatives.. Conclusion: In conclusion, the literature collectively emphasizes the critical need for heightened awareness and education regarding the red flag signs and symptoms of early-onset colorectal cancer. There is a clear call for improved diagnostic protocols and screening strategies to enhance early detection and treatment outcomes for this vulnerable population. Addressing both patient and healthcare provider awareness is essential to mitigate delays in diagnosis and improve prognosis for young patients with EOCRC